2009
DOI: 10.1186/1479-5876-7-15
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility investigation of allogeneic endometrial regenerative cells

Abstract: Endometrial Regenerative Cells (ERC) are a population of mesenchymal-like stem cells having pluripotent differentiation activity and ability to induce neoangiogenesis. In vitro and animal studies suggest ERC are immune privileged and in certain situations actively suppress ongoing immune responses. In this paper we describe the production of clinical grade ERC and initial safety experiences in 4 patients with multiple sclerosis treated intravenously and intrathecally. The case with the longest follow up, of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 42 publications
1
81
0
1
Order By: Relevance
“…Furthermore, numerous preclinical studies have revealed that administration of MenSCs to injured tissues in situ or via intravenous injection induced structural restoration as well as functional improvements in heart failure (Bockeria et al 2013, Jiang et al 2013 and critical limb ischemia (Murphy et al 2008). The similar outcomes were observed in several clinical studies (Zhong et al 2009, Ichim et al 2010a. However, there was no report about MenSCs transplantation for the treatment of IUAs, which was an intractable gynecological disease in assisted reproductive technology.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, numerous preclinical studies have revealed that administration of MenSCs to injured tissues in situ or via intravenous injection induced structural restoration as well as functional improvements in heart failure (Bockeria et al 2013, Jiang et al 2013 and critical limb ischemia (Murphy et al 2008). The similar outcomes were observed in several clinical studies (Zhong et al 2009, Ichim et al 2010a. However, there was no report about MenSCs transplantation for the treatment of IUAs, which was an intractable gynecological disease in assisted reproductive technology.…”
Section: Discussionmentioning
confidence: 55%
“…Notwithstanding, the use of menstrual blood-derived stem cells for allogeneic transplantation may be an equally potential approach to cell therapy, along the line of investigations on therapeutic indications rendered by stem cells harvested from umbilical cord or bone marrow. Of note, menstrual bloodderived stem cells, referred to as endometrial regenerative cells (ERC), have been shown to be safe when transplanted intravenously and intrathecally in 4 patients with multiple sclerosis, characterized by absence of immunological reactions or treatment-associated adverse effects [68].…”
Section: Figmentioning
confidence: 99%
“…Taking note of reports that TGF beta is normally fulfills a key function in regulating the cyclical nature of endometrial proliferative activity [7,35], that TGF beta is of fundamental importance in the cooperative interaction with the immune system in the management of angiogenesis in the endometrium [36], and also plays a major role in the repair of post-traumatic uterine tissue [3], we should recognize the relevance of the selected areas of research, both for theoretical medicine, as well as for implications in public health practice. The data obtained from the use of sodium chloride to stimulate production of TGF beta in the group of animals exposed to barium sulfate provide additional support for this conclusion.…”
Section: Discussionmentioning
confidence: 99%